Recent advances and perspectives of CeO2-based catalysts: Electronic properties and applications for energy storage and conversion - Wang, Xianwei; Wang, Jingyi; Sun, Yafei; Li, Kanghui; Shang, Tongxin; Wan, Ying (Frontiers in Chemistry, 2022)
Cerium dioxide (CeO2, ceria) has long been regarded as one of the key materials in modern catalysis, both as a support and as a catalyst itself. Apart from its well-established use (three-way catalysts and diesel engines), CeO2 has been widely used as a cocatalyst/catalyst in energy conversion and storage applications. The importance stems from the oxygen storage capacity of ceria, which allows it to release oxygen under reducing conditions and to store oxygen by filling oxygen vacancies under oxidizing conditions. However, the nature of the Ce active site remains not well understood because the degree of participation of f electrons in catalytic reactions is not clear in the case of the heavy dependence of catalysis theory on localized d orbitals at the Fermi energy EF. This review focuses on the catalytic applications in energy conversion and storage of CeO2-based nanostructures and discusses the mechanisms for several typical catalytic reactions from the perspectives of electronic properties of CeO2-based nanostructures. Defect engineering is also summarized to better understand the relationship between catalytic performance and electronic properties. Finally, the challenges and prospects of designing high efficiency CeO2-based catalysts in energy storage and conversion have been emphasized.